2020
DOI: 10.1038/s42003-020-01334-0
|View full text |Cite
|
Sign up to set email alerts
|

The genetic architecture of appendicular lean mass characterized by association analysis in the UK Biobank study

Abstract: Appendicular lean mass (ALM) is a heritable trait associated with loss of lean muscle mass and strength, or sarcopenia, but its genetic determinants are largely unknown. Here we conducted a genome-wide association study (GWAS) with 450,243 UK Biobank participants to uncover its genetic architecture. A total of 1059 conditionally independent variants from 799 loci were identified at the genome-wide significance level (p < 5 × 10−9), all of which were also significant at p < 5 × 10–5 in both sexes. These v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
117
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(126 citation statements)
references
References 61 publications
0
117
0
Order By: Relevance
“…In this study, a total of 156 potential ALM-associated SNPs mapping to 15 chromosomes were identified by cFDR (Supplementary Figure 2 and Supplementary Table 3). We compared the SNPs found to be significant by cFDR with previous GWAS findings (Supplementary Table 4) and the latest findings by Pei et al (10). Eight LM-associated SNPs (rs12284933, rs12741884, rs3765350, rs6591341, rs6726821, rs754388, rs917727 and rs9525638) reported by previous GWASs were replicated by cFDR (SNPs marked * in Supplementary Table 3), 66 ALM SNPs identified as significant by cFDR (SNPs marked ** in Supplementary Table 3) exhibited high LD with previouslyconfirmed LM-associated SNPs.…”
Section: Novel Potential Alm-associated Snps Identified By Cfdrmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a total of 156 potential ALM-associated SNPs mapping to 15 chromosomes were identified by cFDR (Supplementary Figure 2 and Supplementary Table 3). We compared the SNPs found to be significant by cFDR with previous GWAS findings (Supplementary Table 4) and the latest findings by Pei et al (10). Eight LM-associated SNPs (rs12284933, rs12741884, rs3765350, rs6591341, rs6726821, rs754388, rs917727 and rs9525638) reported by previous GWASs were replicated by cFDR (SNPs marked * in Supplementary Table 3), 66 ALM SNPs identified as significant by cFDR (SNPs marked ** in Supplementary Table 3) exhibited high LD with previouslyconfirmed LM-associated SNPs.…”
Section: Novel Potential Alm-associated Snps Identified By Cfdrmentioning
confidence: 99%
“…For example, loci are present in TRHR (5), GLYAT (6), PRDM16 (7) and TNRC6B (8). Furthermore, the latest large-scale GWAS has just identified and replicated five loci strongly associated with LM at a genome-wide level of significance (9), and a recent ALM GWAS study identified 1059 conditionally independent variants from 799 loci with a genome-wide significance level (p <5 × 10 −9 ) using the UKB cohort (10). These findings help us better understand the genetic background of sarcopenia, but because of the high heritability of LM, the current findings are extremely limited, a missing heritability is evident.…”
Section: Introductionmentioning
confidence: 99%
“…The GRS deployed by Li et al explains less than 1% of the heritability of lean mass and did not correlate with lean mass in POUNDS lost study participants 13,14 . A more recent study identified 1059 SNPs at 799 loci, associated with BIA‐measured appendicular lean mass in both sexes, adjusted for covariates including appendicular fat mass and age 12 . Together, these explain ~15.5% of the heritability of appendicular lean mass (which correlates with total lean mass) 12 .…”
mentioning
confidence: 95%
“…A more recent study identified 1059 SNPs at 799 loci, associated with BIA‐measured appendicular lean mass in both sexes, adjusted for covariates including appendicular fat mass and age 12 . Together, these explain ~15.5% of the heritability of appendicular lean mass (which correlates with total lean mass) 12 . These variants can potentially be used to investigate whether genetically determined appendicular lean mass and/or skeletal muscle mass is causally associated with response to low‐fat diet through Mendelian randomization (MR) analyses.…”
mentioning
confidence: 99%
See 1 more Smart Citation